Rubber toughened recycled polyethylene terephthalate for material extrusion additive manufacturing - Zander, Nicole E; Boelter, Zachary R (Polymer international, 2021)
Plastic packaging materials represent a new class of low‐cost and sustainable additive manufacturing feedstocks. Recycled polyethylene terephthalate (PET) has been shown to be a robust material for material extrusion additive manufacturing, with mechanical properties comparable with acrylonitrile‐butadiene‐styrene. However, due to PET's high crystallinity, it is generally a brittle material and can be subject to premature fracture. It is well known that the addition of rubbers can serve to toughen PET. In this work, micronized rubber powder, as well as non‐reactive and functionalized styrene‐ethylene‐butadiene‐styrene (SEBS) elastomers were compounded with recycled PET. Tensile strength was not significantly affected, but toughness increased 85% with the addition of 5 wt% rubber, 350% with SEBS and over 550% with maleic anhydride functionalized SEBS compared to neat recycled PET. Fracture surface analysis revealed evidence of ductile fracture and cavitation in the rubber toughened samples. Published 2020. This article is a U.S. Government work and is in the public domain in the USA Recycled polyethylene terephthalate (PET) was toughened with rubber to make a new feedstock for material extrusion additive manufacturing. Toughness increased over 550% with the addition of maleic anhydride functionalized styrene‐ethylene‐butadiene‐styrene.